1996
DOI: 10.1074/jbc.271.41.25220
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at Domain II, Loop 3, of Bacillus thuringiensis CryIAa and CryIAb δ-Endotoxins Suggest Loop 3 Is Involved in Initial Binding to Lepidopteran Midguts

Abstract: Alanine substitutions of loop 3 residues, 438 SGF-SNS 443 , of CryIAb toxin were constructed to study the functional role of these residues in receptor binding and toxicity to Manduca sexta and Heliothis virescens. Experiments with trypsin and insect gut juice enzyme digestions of mutant toxins showed that these mutations did not produce any gross structural changes to the toxin molecule. Bioassay data showed that mutant G439A (alanine substitution of residue Gly 439 ) and F440A significantly reduced toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
68
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 33 publications
1
68
0
Order By: Relevance
“…It had previously been shown that loop regions of domain II harbor receptor-binding epitopes in several insecticidal Cry toxins (23,39,41,45,53). It has also been shown that some mutations in loop regions do not affect initial receptor binding, as measured by competition binding, but affect irreversible binding, suggesting that they affect insertion of the toxin into the membrane (39,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had previously been shown that loop regions of domain II harbor receptor-binding epitopes in several insecticidal Cry toxins (23,39,41,45,53). It has also been shown that some mutations in loop regions do not affect initial receptor binding, as measured by competition binding, but affect irreversible binding, suggesting that they affect insertion of the toxin into the membrane (39,53).…”
Section: Discussionmentioning
confidence: 99%
“…A mutation in loop 2 of Cry1Ab decreases the toxicity to Manduca sexta by affecting irreversible binding, but the same mutant affects neither toxicity nor binding affinity to Heliothis virescens (37). On the other hand, alanine substitutions of loop 3 residues G439 and F440 in Cry1Ab affect the initial receptor binding and toxicity in both M. sexta and H. virescens (41). These loops are proposed to be exceptional targets for genetic engineering to create more potent toxins with diverse insect specificity (38).…”
mentioning
confidence: 99%
“…Binding of Cry1Ab toxin with Bt-R 1 facilitates removal of helix ␣-1, triggering toxin oligomerization (2). The oligomer gains binding affinity to the second receptor, APN, and this interaction enhances insertion of the oligomer into the membrane (3,40). We previously hypothesized that sequential interaction of the Cry1Ab toxin with the two receptors involves structural changes of binding epitopes upon oligomerization (16).…”
Section: Discussionmentioning
confidence: 99%
“…Published data regarding the role of this binding region in the interaction with both receptor molecules are incomplete because binding of loop 3 mutant oligomers with the two receptor molecules was not previously analyzed. Mutagenesis studies of Cry1Ab and Cry1Ac loop 3 previously performed indicated that this amino acid region was important for binding with M. sexta BBMV and toxicity (40,41). In addition, alanine substitutions of loop 3 residues in Cry1Ab and Cry1Ac toxins showed a correlative effect on APN binding, suggesting that their effects on toxicity were due to defects in this binding (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Domain I is involved in membrane insertion and pore formation (5,21,25,43). Domain II plays a role in binding to the insect brush border membranes (16,39,42,44,46,61,62,63,64,72,76) or receptor molecules (23). Domain III is involved in several functions, including determination of insect specificity (8,9,10,38,39,49), recognition of N-acetylgalactosamine (GalNAc) on receptor molecules by a lectin-like structure (4,30,31,36,40), proteolytic protection (43), and ion channel conductivity (6,69,75).…”
mentioning
confidence: 99%